Buttonhole and Edge Sewing Machine Technology Training to Increase the Quality Production of Small Convection Creative Industry in Probolinggo - Rahmansyah, Ahmad Iskandar; Muhammad, Alief; Hendra, Joni; Basit, Abdul; Masluha, Siti; Prasetiyo, Dani Hari Tuggal (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Based on the culture of new clothes on the New Year, Eid, and other special days, the demand for convection products will increase drastically. This condition is a big obstacle for small businesses in the creative industry in Indonesia, especially in Probolinggo. Increasing the amount of convection production in Probolinggo is by applying new technologies to accelerate the production. If convection production, both custom and general order, can be made quickly, the amount of production will increase. A buttonhole sewing machine is a machine that has the ability to embroider and buttonhole automatically. Edge sewing machine, a machine that works as a tool that is able to sew and smooth the edges of the fabric automatically. With these two machines, convection products will be faster. Both machine training service activities were carried out well. The results made using a buttonhole sewing machine show a good and short level of neatness. Edge sewing machines also provide satisfactory results. To sew and tidy up the fabric, it can be done quickly and neatly. All forms of service activities are carried out to be able to solve the problems experienced by small business partners in the creative convection industry in Probolingo.